2008
DOI: 10.1063/1.2908218
|View full text |Cite
|
Sign up to set email alerts
|

Structural disordering process of an amorphous alloy driven by the elastostatic compression at room temperature

Abstract: This study demonstrates that permanent deformation results when an amorphous alloy is subjected to a stress below yield at room temperature. The resultant deformation was observed to be homogeneous and is thought to occur as a result of the structural disordering, in which densely packed short-range ordered clusters break down to form new, loosely packed ones. It was found that this disordering process is irreversible even if the applied stress is removed, resulting in the creation of excess free volume. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…After their report, a new analytical approach using molecular dynamics (MD) simulation and reverse Monte-Carlo (RMC) modeling 5) against the results of X-ray diffraction and X-ray absorption spectroscopy have allowed us to discuss the structural features in more detail, and the overall preference for Cuand Zr-centered icosahedral units has been suggested in Cu 64:5 Zr 35:5 and Cu 61:8 Cu 38:2 amorphous alloys. 6) This geometrical feature was also confirmed by MD simulations, 7,8) and the increase of icosahedral short-range ordering at the Cu-rich region of a Zr-Cu binary system has been discussed in terms of the packing density. 8) On the other hand, Zetterström et al have reported in 2007 the low probability of icosahedral short-range ordering in Zr 50 Cu 50 amorphous sample, based on the results of X-ray diffraction and neutron diffraction coupled with RMC simulation.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…After their report, a new analytical approach using molecular dynamics (MD) simulation and reverse Monte-Carlo (RMC) modeling 5) against the results of X-ray diffraction and X-ray absorption spectroscopy have allowed us to discuss the structural features in more detail, and the overall preference for Cuand Zr-centered icosahedral units has been suggested in Cu 64:5 Zr 35:5 and Cu 61:8 Cu 38:2 amorphous alloys. 6) This geometrical feature was also confirmed by MD simulations, 7,8) and the increase of icosahedral short-range ordering at the Cu-rich region of a Zr-Cu binary system has been discussed in terms of the packing density. 8) On the other hand, Zetterström et al have reported in 2007 the low probability of icosahedral short-range ordering in Zr 50 Cu 50 amorphous sample, based on the results of X-ray diffraction and neutron diffraction coupled with RMC simulation.…”
Section: Introductionsupporting
confidence: 49%
“…This characteristic feature in the nearest-neighbor region could not be found in the crystalline phases, and is suggested to be a very important atomic arrangement for stabilizing the amorphous structure. [6][7][8]24,25) Additionally, the chemical oscillatory structure composed of alternating Cu-rich and Zr-rich coordination shells can be proposed as an example of middle-range ordering. The structural information on Zr 50 Cu 50 amorphous alloy obtained in this work represents a first and reliable step toward uncovering the direct link between the atomic-scale structure and the characteristic properties of amorphous alloys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also evident that the fraction of ICO inside shear bands is significantly lower than the undeformed matrix in MGs [26,27]. Plastic deformation or elastic deformation close to the yield stress can introduce irreversible structural change to the MGs [28][29][30][31]. (3) The atomic mobility is found to be closely related with the ICO in both Cu-Zr MGs and supercooled liquids [32].…”
Section: Introductionmentioning
confidence: 89%
“…Uniaxial compression at constant load (well within the elastic range) has been applied for several hours to bulk metallic glass rods at room temperature [18][19][20][21][22][23][24]. On application of the load, the sample shows an instantaneous elastic strain ε e , then, with continued loading time, a time-dependent anelastic strain ε a that saturates, and finally a linearly increasing viscoplastic strain ε v .…”
Section: Stored Energy From Elastostatic Loadingmentioning
confidence: 99%